Resolution auto-adaptative par elements finis de problemes de diffusion fortement non lineaires - Bonelli, Stephane; Golay, Frederic; Debordes, Olivier (European Journal of Computational Mechanics, 1993)
For many non stationnary problems, the time steps necessary to finite element computing are most of the time very difficult to determine. Thus, we propose an automatic method and we apply it to solve diffusion's equations. After analysing on simple cases the principe of this method, we solve two problems hightly non linear. The first one consists on the curing process of a composite structure (thermo-chemical coupling), and the second consists on the simulation of an earthdam's filling (flow in porous media).